Analisis Kinerja Keuangan Pada PT. Sekar Bumi TBK Pendekatan Rasio Keuangan - Fitria, Nita; Fitri, Maisa; Shabri, Husni; Shobirin, Khairulis (Jurnal Manajemen Bisnis Syariah, 2025)
The purpose of this study was to analyze the financial performance of PT Sekar Bumi Tbk for the period 2019-2022. The type of research used is field research by taking data from the official website of the Indonesia Stock Exchange. The data collection technique of this research is documentation technique in the form of financial statements of PT Sekar Bumi Tbk. The data analysis technique uses financial ratio analysis. The results of this study are the financial performance of PT Sekar Bumi Tbk in 2019-2022 from the liquidity ratio seen from the company's current ratio in good condition. Quick ratio the company is in good condition. The company's cash ratio is also in good condition. The solvency ratio in 2019-2022, the company's financial performance shows good conditions. The solvency ratio on the debt to asset ratio, the company is in good condition. The company's debt to equity ratio is in good condition. The ratio of total assets to company debt is in good condition. The profitability ratio, the company's net profit margin is in good condition. The company's gross profit margin is in good condition. The company's operating profit margin is in good condition. Return on investment, the company is in good condition. The company's return on equity is in good condition. The activity ratio, the company's receivable turnover is in good condition. The company's inventory turnover is in good condition